The Efficacy of Secondary Prophylaxis in Reducing the Progression of Rheumatic Heart Disease in Children and Adolescents in Endemic Regions: A Systematic Review - Rizky Handayani; Dita Ayu Dewi Laras Sati; Agustinus Mahardhika Sarayar (The International Journal of Medical Science and Health Research, 2026)
Introduction: Rheumatic heart disease (RHD), a chronic and debilitating sequela of Group A Streptococcus infection, persists as a leading cause of cardiovascular morbidity and mortality among children and young adults in endemic regions. Secondary antibiotic prophylaxis is the cornerstone of management, aimed at preventing recurrent episodes of acute rheumatic fever (ARF) and halting the progression of cardiac valvular damage. This systematic review critically evaluates the body of evidence supporting the effectiveness of this vital intervention in pediatric and adolescent populations. Methods: A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases were systematically searched for randomized controlled trials (RCTs) and observational studies published up to October 2024. Studies were included if they evaluated antibiotic prophylaxis compared to placebo, no treatment, or alternative prophylactic regimens in children and adolescents with a diagnosis of ARF or RHD in endemic settings. A comprehensive set of outcomes was assessed, including echocardiographic progression of disease, ARF recurrence, all-cause and cardiovascular mortality, major cardiac events, and adverse events. The methodological quality of included studies was rigorously assessed using the Cochrane Risk of Bias 2 tool for RCTs and the Newcastle-Ottawa Scale for observational studies. Results: A total of 18 studies, comprising 3 pivotal RCTs and 15 observational cohort and registry studies, met the stringent inclusion criteria. High-certainty evidence from a recent, large-scale RCT conducted in Uganda (Beaton et al., 2021) demonstrated that intramuscular benzathine penicillin G (BPG) significantly reduces the risk of echocardiographic progression in children with latent RHD compared to no treatment (Risk Difference -7.5%; 95% CI, -10.2 to -4.7; p<0.001). A comprehensive 2024 Cochrane review (Bray et al., 2024), which included a meta-analysis of historical trials, confirmed that intramuscular BPG is substantially superior to oral antibiotic regimens for the prevention of ARF recurrence (Risk Ratio 0.07; 95% CI, 0.02 to 0.26). The body of evidence from observational studies consistently reveals a strong and significant correlation between poor adherence to secondary prophylaxis and increased rates of ARF recurrence, RHD progression, and adverse cardiac outcomes. Discussion: The collective evidence unequivocally supports the use of secondary prophylaxis with intramuscular BPG as a highly effective clinical intervention. The recent validation of its efficacy in the early, latent stage of RHD provides a compelling scientific and ethical rationale for the integration of echocardiographic screening into public health programs in high-risk settings. However, the profound gap between the proven efficacy of this therapy and its real-world effectiveness is a critical concern. This gap is driven almost entirely by poor patient adherence, which remains the single greatest barrier to the successful control and eventual elimination of RHD. Conclusion: Secondary antibiotic prophylaxis, particularly with long-acting intramuscular BPG, is unequivocally effective in reducing the progression of RHD and preventing its devastating sequelae in children and adolescents. The focus of future research and public health initiatives must pivot from confirming efficacy to addressing the complex challenges of implementation. Overcoming the profound and multifaceted barriers to treatment adherence is the most urgent priority to translate this proven intervention into tangible and equitable public health gains.